(untitled) (Research, Society and Development, 2020)
Schizophrenia is a chronic mental illness quite present in Brazilian society, but it does not have the care and attention necessary to make the patient’s well-being satisfactory. It has a very complex pharmacodynamics, where without proper care, can cause adverse effects that may harm the health of the patient. Therefore, the objective of this study is to evaluate in the last five years the leukogram profile of patients with refractory schizophrenia who use clozapine assisted in the Specialized Component of Pharmaceutical Care of Piauí, by analyzing data that will be collected through the evaluation of medical records. analyzing and verifying that the leukogram levels of these patients are within the parameters recommended by the literature. They were then checked in the SOFTWARE PRISMA 6.0 program. The results showed that of the analyzed charts, regarding gender, 64% were men and 36% were women. There was an incidence of agranulocytosis and the highest age was 31 to 40 years. Drug change and the incidence of neutropenia, thrombocytopenia and eosinophilia were also observed in some patients. Thus, it can be suggested that patients with refractory schizophrenia treated in the Specialized Component of Pharmaceutical Care of Piauí, are having a multiprofessional follow-up, especially the pharmacist who provides patient care at the time of dispensation, very effective.